2010
DOI: 10.1007/s11606-010-1549-9
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Chronic Hepatitis B Treatment Guideline Recommendations for Laboratory Monitoring of Patients Who Are Not Receiving Antiviral Treatment

Abstract: BackgroundHepatitis B virus (HBV) DNA and alanine aminotransferase (ALT) levels predict future complications in chronic hepatitis B (CHB) patients. To determine when to initiate antiviral therapy, treatment guidelines recommend monitoring of HBV DNA and ALT levels at least annually. This study aimed to assess adherence to treatment guideline-recommended monitoring of CHB patients not receiving antiviral treatment and to identify predictors of laboratory monitoring and subsequent initiation of antiviral therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…Almost one-third of inactive carriers in our study did not have monitoring of ALT at least every 12 months, although gastroenterologists were more likely to perform timely monitoring than PCPs. This finding is consistent with a large retrospective study assessing adherence to AASLD CHB laboratory monitoring guidelines, which found that ∼ 50% of patients failed to undergo timely ALT assessment (5). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Almost one-third of inactive carriers in our study did not have monitoring of ALT at least every 12 months, although gastroenterologists were more likely to perform timely monitoring than PCPs. This finding is consistent with a large retrospective study assessing adherence to AASLD CHB laboratory monitoring guidelines, which found that ∼ 50% of patients failed to undergo timely ALT assessment (5). …”
Section: Discussionsupporting
confidence: 90%
“…The American Association for the Study of Liver Diseases (AASLD) has published guidelines to assist health-care providers in the management and treatment of CHB, including setting standards for timely alanine aminotransferase (ALT) and viral load monitoring for inactive carriers and immune-tolerant patients (i.e., phases that do not require treatment), liver biopsy to guide treatment decisions, criteria for treatment initiation, screening for HCC, and testing for hepatitis A, hepatitis C, and HIV co-infections (2). A previous study has shown that less than one-third of CHB patients receive appropriate laboratory screening (5). Another study of gastroenterologists' HCC screening practices for CHB patients showed that only 60% performed at least annual HCC screening (6).…”
Section: Introductionmentioning
confidence: 99%
“…(8)(9)(10) In addition, poor monitoring of chronic HBV patients has led to the delayed initiation of antiviral therapy, leaving patients at risk for disease progression. (11) Similar patterns have been recognized in the community setting, where a minority of HBV patients, including those with cirrhosis, had low rates of antiviral therapy initiation and HCC screening. (12) However, no published US studies to date have examined HBV care quality among a national sample.…”
supporting
confidence: 52%
“…Similar to previous studies, we found low adherence to recommended laboratory testing and significant gaps in the clinical recognition of HBV diagnosis and subsequent follow-up care. (8)(9)(10)(11) A minority of patients had the HBV diagnosis code entered into the medical record by providers, and fewer than half had confirmatory testing 6 months after the initial HBsAg result. Although patients with confirmed chronic HBV infection had higher rates of recommended laboratory testing, testing rates were still suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10 years, screening and treatment of HCV in the VA health care system have received a great deal of attention, while little, if any, focus has been directed to the diagnosis and management of chronic HBV despite the high hepatitis B surface antigen seroprevalence among veterans. Other studies have evaluated care delivery and outcomes for civilian segments of the US population with chronic HBV using large administrative claims data sets or manual review of individual patient records (Table ) . Regardless of the research methodology employed, these retrospective studies have consistently found that rates of antiviral therapy and HCC surveillance are suboptimal and that specialty care is associated with a greater likelihood of receiving recommended care.…”
Section: Studies Of Care Quality Metrics In Americans With Chronic Hbvmentioning
confidence: 99%